Efficacy of hip strengthening on varus thrust in knee osteoarthritis - Heba E Mohamed; Enas F Youssef; Abd-Elrahman A Rezk; Nabil A Mohamed (Universidad de Murcia, 2023)
Article accepted. The article will be published here soon. Pending final quality checks.